2015
DOI: 10.1002/smll.201500874
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Force Microscopy in Liquids

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: In this work, the use of magnetic force microscopy (MFM) to acquire images of magnetic nanostructures in liquid environments is presented. Optimization of the MFM signal acquisition in liquid media is performed and it is applied to characterize the magnetic signal of magnetite nanoparticles. The ability for detecting magnetic nanostructures along with the well-known capabilities of AFM in liquids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
(49 reference statements)
1
25
1
1
Order By: Relevance
“…We employed a cantilever holder that minimizes the spurious resonance frequencies that often appear when working in liquids (see ESI of ref. 39). This allowed us to determine the resonance frequency from a frequency sweep in good agreement with the resonance frequency value obtained by measuring the cantilever thermal noise.…”
mentioning
confidence: 99%
“…We employed a cantilever holder that minimizes the spurious resonance frequencies that often appear when working in liquids (see ESI of ref. 39). This allowed us to determine the resonance frequency from a frequency sweep in good agreement with the resonance frequency value obtained by measuring the cantilever thermal noise.…”
mentioning
confidence: 99%
“…Imaging magnetic nanoparticles in liquid served as a proof of principle for using MFM to image magnetic nanoparticles within cells in order to better understand their distribution and behavior in a physiologically relevant environment. Another recent study published from the Universidad Autonoma de Madrid in Spain reported successful MFM imaging of nanoparticles in liquid [23]. In this study, MFM was used to not only image these nanoparticles, but to optimize the MFM signal acquisition in liquid media so that it could be applied to the characterization of magnetic nanoparticles and their magnetic signals.…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 97%
“…Perhaps most notably, MFM is capable of operating under ambient conditions, at varying temperatures, ultrahigh vacuums, as well as liquid environments [3,23] while still providing resolution to less than ten nanometers. This is essential because it allows magnetic nanoparticles to be localized and characterized in vitro [24] or inside polymer films and cell-like systems [3,25,26].…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 A common downside of all these standard characterization techniques lies on the fact that they only provide average information over a very large number of NPs. S2) [15][16][17][18][19] MFM has proved to be a versatile technique, by means of which it is possible to study the real time evolution of the magnetic domains by variable-field MFM (VF-MFM) 20 or to characterize the evolution of MFM contrast versus the tipsample distance by the 3D mode, allowing a complete characterization of the small structures. S1), thermogravimetric curves for samples R11 and R49 (Fig.…”
Section: Introductionmentioning
confidence: 99%